Economics and Law - Abdulkhasan A. M., Shpak A. S., Mashkin A. L., Gogolina E. S., Glagoleva S. V., Miasoedov C. A., Stenkina E. N., Stenkina E. N., Sakharova L. A., Sakharova L. A., Borovkova V. A., Borovkova V. A., Matasova I. I. (Economics and Law, 2020)
the article examines the problems of landscaping of urban areas and securing their legal status as one of the main areas of activity of the municipal economy to create conditions for a high standard of living of the population. The empirical base was provided by regulations, scientific articles and literature, statistical data, reports, and the results of a sociological study conducted on the territory of the Novorossiysk's Ministry of Defense. The analysis of the material allowed us to study the experience of local authorities in this area and formulate proposals to improve their effectiveness.
Keywords: городские территории; зеленые насаждения; планирование территории; кадастровый учет; особо охраняемые природные территории; лесопарковый зеленый пояс; urban areas; green spaces; territory planning; cadastral registration; specially protected natural areas; forest Park green belt